2014
DOI: 10.1364/ol.39.006126
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear conversion efficiency in Kerr frequency comb generation

Abstract: We analytically and numerically investigate the nonlinear conversion efficiency in ring microresonator-based mode-locked frequency combs under different dispersion conditions. Efficiency is defined as the ratio of the average round trip energy values for the generated pulse(s) to the input pump light. We find that the efficiency degrades with growth of the comb spectral width and is inversely proportional to the number of comb lines. It depends on the cold-cavity properties of a microresonator only and can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
99
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(104 citation statements)
references
References 27 publications
(36 reference statements)
5
99
0
Order By: Relevance
“…Soliton formation in crystalline materials has not shown any evidence [6,11]. Recently, for amorphous silica-and SiN-based microresonators, the Raman effect was estimated by numerical simulations [29][30][31], and it was found that a comb spectral shift can occur when a Ramannonlinearity assisted single temporal dissipative soliton is formed. In this letter, we report for the first time to the authors' best knowledge the direct experimental observation of Raman induced soliton self-frequency shift in microresonator solitons.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Soliton formation in crystalline materials has not shown any evidence [6,11]. Recently, for amorphous silica-and SiN-based microresonators, the Raman effect was estimated by numerical simulations [29][30][31], and it was found that a comb spectral shift can occur when a Ramannonlinearity assisted single temporal dissipative soliton is formed. In this letter, we report for the first time to the authors' best knowledge the direct experimental observation of Raman induced soliton self-frequency shift in microresonator solitons.…”
mentioning
confidence: 99%
“…Theory and numerical simulations -We numerically simulate the Kerr comb generation in SiN microresonators, based on LLE [6,7,36,37], but include the Raman effect [29][30][31]:…”
mentioning
confidence: 99%
“…A generalized LL equation that takes into account higher order dispersion was introduced in [75,135]. Raman scattering as well as self-steepening terms were added to this equation in [136][137][138].…”
Section: Lugiato-lefever (Forced Damped Nonlinear Schrödinger) Equationmentioning
confidence: 99%
“…The low efficiency of the nonlinear process resulting in the mode locked Kerr comb is one of them [137]. The efficiency, defined as the ratio of the pump power and averaged pulse train power, degrades with growth of the comb spectral width, and is inversely proportional to the number of comb lines.…”
Section: Unsolved Problemsmentioning
confidence: 99%
“…In order to stimulate experiments, in the second part of the article we consider a specific realistic fiber ring cavity system. We finally note that this work can also shed new light on the peculiar role that plays the Raman effect on the generation of frequency combs in high-finesse optical micro-cavities [72][73][74][75][76], a subject of current intense investigations in relation with the important issue of the coherence properties of frequency combs [77][78][79][80][81].…”
Section: Introductionmentioning
confidence: 99%